(untitled) (Research, Society and Development, 2021)
The spread of COVID-19 in 2020 was the most serious health threat in the world since the so-called Spanish Flu in 1918. With almost every country affected in the world, 100 million confirmed cases, more than 2 million deaths and a significant contraction in the world’s gross domestic product, the pandemic brought enormous human and economic costs. Thus, the aim of this article is to report the musculoskeletal consequences after COVID-19, through a literature review. Rehabilitation programs must be adapted to the severity of the disease, age group, previous fitness levels and pre-existing comorbidities. For the proper rehabilitation of patients, they will need new knowledge and skills about COVID-19. Therefore, it is expected that patients affected by COVID- 19 suffer musculoskeletal consequences as a result of the inflammatory process and loss of bone and muscle mass caused by immobility, generating motor disabilities that have not yet been quantified. It is important to understand the clinical implications caused by COVID-19 in order to have better rehabilitation strategies for these patients. The aim of this study was to conduct a reflective analysis of the impact of COVID-19 on the immune, neuromuscular and musculoskeletal system and its rehabilitation process.